Additions to the Tanaidomorpha (Crustacea: Tanaidacea) from mud volcanoes and coral mounds of the Gulf of Cadiz and Horseshoe Continental Rise - Esquete, Patricia; Cunha, Marina R. (Zootaxa, 2018)
The Tanaidacea collection from various research cruises carried out in the Gulf of Cadiz and Horseshoe Continental Rise between 2004 and 2012 yielded four species new to science that are described herein. Two belong to genera recorded for the first time since the original descriptions of their type species: Cetiopyge, described from the Gulf of Mexico and Gamboa from shallow waters of Macaronesia. The other two belong to the genera Collettea and Paragathotanais, both with a worldwide distribution. Additionally, specimens of Tumidochelia uncinata are described and illustrated to complete previous descriptions. Identification keys to all known genera of Nototanaidae, and the Eastern Atlantic species of Paragathotanais and Collettea are provided. This works raises the number of tanaidacean species known from the deep-sea habitats in the study region to a total of 22.